PENGARUH DISIPLIN KERJA, KOMPETENSI, BUDAYA ORGANISASI, DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN BANJARSARI KOTA SURAKARTA - Diah Ayu Munntari; Sunarso Sunarso; Retno Susanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2020)
This research aims to analyze the influence of work discipline, competence, organizational culture and work facilities to the performance of employees of Banjarsari District office of Surakarta City. This research uses the survey method, the type of data used is qualitative data and quantitative data, the data sources used primary data and secondary data. The population and samples in this study were all employees of the Banjarsari district office of Surakarta City which amounted to 32 people, so it is a census study. Data collection methods used: questionnaires and documentation. Data analysis techniques used validity tests, reliability tests, classical assumption tests, multiple linear regression analyses, t tests, F tests and coefficient of determinations. The results of the study were concluded that: the work discipline has significant effect on the employee performance of Banjarsari District office in Surakarta City. The competency has significant effect on the employee performance of Banjarsari district office in Surakarta. The organizational culture has significant effect on the employee performance of Banjarsari district office in Surakarta. The facility has significant effect on the employee performance of Banjarsari District office in Surakarta City.